Parametric Methods for Dynamic 11 C-Phenytoin PET Studies - Mansor, Syahir; Yaqub, Maqsood; Boellaard, Ronald; Froklage, Femke E.; de Vries, Anke; Bakker, Esther D.M.; Voskuyl, Rob A.; Eriksson, Jonas; Schwarte, Lothar A.; Verbeek, Joost; Windhorst, Albert D.; Lammertsma, Adriaan A. (Journal of Nuclear Medicine, 2017)
In this study, the performance of various methods for generating quantitative parametric images of dynamic C-phenytoin PET studies was evaluated. Double-baseline 60-min dynamic C-phenytoin PET studies, including online arterial sampling, were acquired for 6 healthy subjects. Parametric images were generated using Logan plot analysis, a basis function method, and spectral analysis. Parametric distribution volume (V ) and influx rate ( ) were compared with those obtained from nonlinear regression analysis of time-activity curves. In addition, global and regional test-retest (TRT) variability was determined for parametric and V values. Biases in V observed with all parametric methods were less than 5%. For , spectral analysis showed a negative bias of 16%. The mean TRT variabilities of V and were less than 10% for all methods. Shortening the scan duration to 45 min provided similar V and with comparable TRT performance compared with 60-min data. Among the various parametric methods tested, the basis function method provided parametric V and values with the least bias compared with nonlinear regression data and showed TRT variabilities lower than 5%, also for smaller volume-of-interest sizes (i.e., higher noise levels) and shorter scan duration.